Corrosion Phenomena and Fatigue Behavior of Clinched Joints: Numerical and Experimental Investigations - Harzheim, Sven; Ewenz, Lars; Zimmermann, Martina; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Lightweight construction has increasingly become the focus of scientific research in recent years, not least due to the constantly increasing fuel price, which is a key factor in the economic viability of many companies. In this respect, the use of hybrid structures, made of dissimilar materials offers many advantages. However, such hybrid structures often have undesirable side effects. For example, brittle intermetallic phases are formed when aluminum and steel are welded. Clinching as a mechanical joining process does not produce such intermetallic phases since the connection is realized through form and force closure. In this process, a punch passes through two or more sheets and forms them into a permanent joint in a die. In the present work, the corrosion phenomena of an aluminum-steel clinched joint have been investigated by both experiments and numerical simulations in order to explain the superior fatigue behavior of pre-corroded joints. Therefore, the clinched joints have been corroded by a three-week salt-spray test. In addition, the electric potential and the von Mises stress are calculated under the assumption of a static loading. The results of both experiments and numerical simulations can explain the improvement in the fatigue behavior of the corroded specimens. This phenomenon can be attributed to the accumulation of corrosion products in small gaps between the joined metal sheets.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

The Influence of Heat Treatment on the Microstructure, Surface Roughness and Shear Tensile Strength of AISI 304 Clinch Joints - Zeuner, André Till; Ewenz, Lars; Kalich, Jan; Schöne, Sebastian; Füssel, Uwe; Zimmermann, Martina (Metals)
Clinching is the manufacturing process of joining two or more metal sheets under high plastic deformation by form and force closure without thermal support and auxiliary parts. Clinch connections are applicable to difficult-to-join hybrid material combinations, such as steel and aluminum. Therefore, this technology is interesting for the application of AISI 304 components, as this material is widely used as a highly formable sheet material. A characteristic feature of AISI 304 is its metastability, i.e., the face-centered cubic (fcc) γ-austenite can transform into a significantly stronger body-centered cubic (bcc) α’-martensite under plastic deformation. This work investigates the effect of heat treatment—a process that involves the formation of an oxidation layer on the sheet surface—on the forming process during joining and the resulting mechanical properties of clinch joints made from AISI 304. For this purpose, different joints made from non-heat treated and heat-treated sheets were examined using classical metallography and advanced SEM techniques, accompanied by further investigations, such as hardness and feritscope measurements. The shear tensile strength was determined, and the fracture behavior of the samples was investigated. Clear influences of heat-treatment-induced surface roughness on the joint geometry and strength were observed.
Keywords: General Materials Science; Metals and Alloys

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Characterisation of Fibre Bundle Deformation Behaviour—Test Rig, Results and Conclusions - Borowski, Andreas; Gröger, Benjamin; Füßel, René; Gude, Maik (Journal of Manufacturing and Materials Processing)
Deformation of continuous fibre reinforced plastics during thermally-assisted forming or joining processes leads to a change of the initial material structure. The load behaviour of composite parts strongly depends on the resultant material structure. The prediction of this material structure is a challenging task and requires a deep knowledge of the material behaviour above melting temperature and the occurring complex forming phenomena. Through this knowledge, the optimisation of manufacturing parameters for a more efficient and reproducible process can be enabled and are in the focus of many investigations. In the present paper, a simplified pultrusion test rig is developed and presented to investigate the deformation behaviour of a thermoplastic semi-finished fiber product in a forming element. Therefore, different process parameters, like forming element temperature, pulling velocity as well as the forming element geometry, are varied. The deformation behaviour in the forming zone of the thermoplastic preimpregnated continuous glass fibre-reinforced material is investigated by computed tomography and the resultant pulling forces are measured. The results clearly show the correlation between the forming element temperature and the resulting forces due to a change in the viscosity of the thermoplastic matrix and the resulting fiber matrix interaction. In addition, the evaluation of the measurement data shows which forming forces are required to change the shape of the thermoplastic unidirectional material with a rectangular cross-section to a round one.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Pin Extrusion for Mechanical Joining from Orbital Formed Tailored Blanks with Local Material Pre-Distribution - Römisch, David; Hetzel, Andreas; Wituschek, Simon; Lechner, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing)
Pin extrusion is a common process to realise pin structures in different geometrical dimensions for a subsequent joining operation. Nevertheless, the process of pin extrusion offers process limits regarding sheet thinning as a consequence of the punch penetration depth into the sheet. Thereby, cracks at the residual sheet thickness can occur during strength tests, resulting in a failure of the complete joint due to severe thinning. Therefore, measures have to be taken into account to reduce the thinning. One possibility is the application of orbital formed tailored blanks with a local material pre-distribution, which allows a higher sheet thickness in the desired area. Within this contribution, the novel approach of a process combination of orbital forming and pin extrusion is investigated. To reveal the potential of a local material pre-distribution, conventional specimens are compared with previously orbital formed components. Relevant parameters such as the residual sheet thickness, the pin height as well as the average hardness values are compared. The results show a significant positive influence of a local material pre-distribution on the residual sheet thickness as well as the resulting pin height. Furthermore, the strain hardening during orbital forming can be seen as an additional advantage. To conclude the results, the process limits of conventional pin extrusion can be expanded significantly by the application of specimens with a local material pre-distribution.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Warmforming Flow Pressing Characteristics of Continuous Fibre Reinforced Thermoplastic Composites - Gröger, Benjamin; Römisch, David; Kraus, Martin; Troschitz, Juliane; Füßel, René; Merklein, Marion; Gude, Maik (Polymers)
The paper presents research regarding a thermally supported multi-material clinching process (hotclinching) for metal and thermoplastic composite (TPC) sheets: an experimental approach to investigate the flow pressing phenomena during joining. Therefore, an experimental setup is developed to compress the TPC-specimens in out-of-plane direction with different initial TPC thicknesses and varying temperature levels. The deformed specimens are analyzed with computed tomography to investigate the resultant inner material structure at different compaction levels. The results are compared in terms of force-compaction-curves and occurring phenomena during compaction. The change of the material structure is characterized by sliding phenomena and crack initiation and growth.
Keywords: Polymers and Plastics; General Chemistry

A Data Driven Modelling Approach for the Strain Rate Dependent 3D Shear Deformation and Failure of Thermoplastic Fibre Reinforced Composites: Experimental Characterisation and Deriving Modelling Parameters - Gerritzen, Johannes; Hornig, Andreas; Gröger, Benjamin; Gude, Maik (Journal of Composites Science)
The 3D shear deformation and failure behaviour of a glass fibre reinforced polypropylene in a shear strain rate range of γ˙=2.2×10−4 to 3.4 1s is investigated. An Iosipescu testing setup on a servo-hydraulic high speed testing unit is used to experimentally characterise the in-plane and out-of-plane behaviour utilising three specimen configurations (12-, 13- and 31-direction). The experimental procedure as well as the testing results are presented and discussed. The measured shear stress–shear strain relations indicate a highly nonlinear behaviour and a distinct rate dependency. Two methods are investigated to derive according material characteristics: a classical engineering approach based on moduli and strengths and a data driven approach based on the curve progression. In all cases a Johnson–Cook based formulation is used to describe rate dependency. The analysis methodologies as well as the derived model parameters are described and discussed in detail. It is shown that a phenomenologically enhanced regression can be used to obtain material characteristics for a generalising constitutive model based on the data driven approach.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Atomic Force Microscope with an Adjustable Probe Direction and Integrated Sensing and Actuation - Schaude, Janik; Hausotte, Tino (Nanomanufacturing and Metrology)
This article presents the application and evaluation of a cantilever with integrated sensing and actuation as part of an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, which is operated in closed-loop intermittent contact mode, is based on two rotational axes that enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion, which ultimately limits the achievable measurement uncertainty of the measuring system. Thus, to reduce the thermal sensitivity of the system, the redesign of the rotational kinematics is mandatory. However, in this article, some preliminary investigations on the application of a self-sensing cantilever with an integrated micro heater for its stimulation will be presented. In previous investigations, a piezoelectric actuator has been applied to stimulate the cantilever. However, the removal of the piezoelectric actuator, which is enabled by the application of a cantilever with an integrated micro heater, promises an essential simplification of the sensor holder. Thus, in the future it might be possible to use materials with a low coefficient of thermal expansion, which are often difficult to machine and therefore only allow for rather simple geometries. Furthermore, because of the creepage of piezoelectric actuators, their removal from the metrology frame might lead to improved metrological characteristics. As will be shown, there are no significant differences between the two modes of actuation. Therefore, the redesigned rotational system will be based on the cantilever with integrated sensing and actuation.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Materials Science (miscellaneous)

A Damage Model for Corrosion Fatigue Due to Hydrogen Embrittlement - Shi, Yuhao; Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Material Modeling and Structural Mechanics)
Predicting the durability of components subjected to mechanical load under environmental conditions leading to corrosion is one of the most challenging tasks in mechanical engineering. The demand for precise predictions increases with the desire of lightweight design in transportation due to environmental protection. Corrosion with its manifold of mechanisms often occurs together with the production of hydrogen by electrochemical reactions. Hydrogen embrittlement is one of the most feared damage mechanisms for metal constructions often leading to early and unexpected failure. Until now, predictions are mostly based on costly experiments. Hence, a rational predictive model based on the fundamentals of electrochemistry and damage mechanics has to be developed in order to reduce the costs. In this work, a first model approach based on classical continuum damage mechanics is presented to couple both, the damage induced by the mechanical stress and the hydrogen embrittlement. An elaborated two-scale model based on the selfconsistent theory is applied to describe the mechanical damage due to fatigue. The electrochemical kinetics are elucidated through the Langmuir adsorption isotherm and the diffusion equation to consider the impact of hydrogen embrittlement on the fatigue. The modeling of the mechanism of hydrogen embrittlement defines the progress of damage accumulation due to the electrochemistry. The durability results like the S-N diagram show the influence of hydrogen embrittlement by varying, e.g. the fatigue frequency or the stress ratio.
Keywords: Hydrogen embrittlement; Fatigue; Continuum damage mechanics; Numerical simulation; Multi-field problem

Long-Term Behavior of Clinched Electrical Contacts - Kalich, Jan; Matzke, Marcus; Pfeiffer, Wolfgang; Schlegel, Stephan; Kornhuber, Ludwig; Füssel, Uwe (Metals)
Joining by forming operations presents powerful and complex joining techniques. Clinching is a well-known joining process for use in sheet metalworking. Currently, clinched joints are focusing on mechanically enhanced connections. Additionally, the demand for integrating electrical requirements to transmit electrical currents will be increased in the future. This integration is particularly important, for instance, in the e-mobility sector. It enables connecting battery cells with electrical joints of aluminum and copper. Systematic use of the process-specific advantages of this joining method opens up the possibility to find and create electrically optimized connections. The optimization for the transmission of electrical currents will be demonstrated for clinched joints by adapting the tool geometry and the clinched joint design. Based on a comparison of the electrical joint resistance, the limit use temperature is defined for the joining materials used based on the microstructural condition and the aging condition due to artificial aging. As a result of the investigations carried out, reliable current transmission at a constant conductor temperature of up to 120 °C can be achieved for clinched copper–copper joints. In the case of pure aluminum joints and mixed joints of aluminum and copper, long-term stable current transmission can be ensured up to a conductor temperature of 100 °C.
Keywords: General Materials Science; Metals and Alloys

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Comparison of two mesh-moving techniques for finite element simulations of galvanic corrosion - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Acta Mechanica)
Galvanic corrosion is a destructive process between dissimilar metals. The present paper presents a constructed numerical test case to simulate galvanic corrosion of two dissimilar metals. This test case is used to study the accuracy of different implementations to track the dissolving anode boundary. One technique is to numerically simulate a mesh displacement based on the prescribed displacement at the anode boundary. The second method is to adjust only the boundary elements. Re-meshing after a certain number of time steps is applied to both implementations. They produce similar results for an electrical and electrochemical field problem. This work shows that mesh smoothing does not result in higher accuracy when modeling a moving anode front. Adjusting only the boundary elements is sufficient when frequent re-meshing is used.
Keywords: Mechanical Engineering; Computational Mechanics

Electrical Contacting of Aluminum Bus Bars Using Clinching and Functional Elements - Füssel, Uwe; Schlegel, Stephan; Reschke, Gregor; Kalich, Jan (SFU/ICAFT 2022)
As a joining-by-forming process, clinching and the use of functional elements enable low-energy joining of components through form, force, and, under certain conditions, material closure. In addition to the transmission of mechanical forces, these joining processes can be qualified for additional electrical contact within the scope of functional integration for electro-mobile applications. For this purpose, maximizing the force and material closure is necessary to ensure a long-term, stable transmission of electrical currents. To this end, the electrical properties of the joints were optimized. The investigations carried out show the long-term behavior under normal operating conditions and the short-circuit case.

Investigations on Combined in situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (The International Journal of Advanced Manufacturing Technology)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
Keywords: Industrial and Manufacturing Engineering; Computer Science Applications; Mechanical Engineering; Software; Control and Systems Engineering

Numerical fatigue life prediction of corroded and non-corroded clinched joints - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Mechanics of Advanced Materials and Structures)
Mechanical clinching is used to create lightweight hybrid structures. In order to estimate the service life of clinched components, its fatigue properties need to be known under different mechanical loading conditions. In addition to fatigue, corrosion is another factor that affects the fatigue life of clinched joints. In the literature, many corrosion and high-cycle fatigue damage models exist. However, little is known about how both phenomena interact in clinched joints. In this article, the influence of galvanic corrosion on clinched EN AW-6014/HCT590X + Z sheets on the fatigue life is investigated by means of numerical simulations and experimental results. An accurate prediction of the Wöhler lines of non-corroded and pre-corroded clinched specimens is shown.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; General Mathematics; Civil and Structural Engineering

Rechnungslegung nach IFRS und HGB: Lehrbuch zur Theorie und Praxis der Unternehmenspublizität mit Beispielen und Übungen - Ruhnke, Klaus; Simons, Dirk; Sievers, Sönke

Asymmetric, non-uniform 3-dB directional coupler with 300-nm bandwidth and a small footprint - Nikbakht, Hamed; Khoshmehr, Mohammad Talebi; van Someren, Bob; Teichrib, Dieter; Hammer, Manfred; Förstner, Jens; Akca, B. Imran (Optics Letters)
Here we demonstrate a new, to the best of our knowledge, type of 3-dB coupler that has an ultra-broadband operational range from 1300 to 1600 nm with low fabrication sensitivity. The overall device size is 800 µm including in/out S-bend waveguides. The coupler is an asymmetric non-uniform directional coupler that consists of two tapered waveguides. One of the coupler arms is shifted by 100 µm in the propagation direction, which results in a more wavelength-insensitive 3-dB response compared to a standard (not shifted) coupler. Moreover, compared to a long adiabatic coupler, we achieved a similar wavelength response at a 16-times-smaller device length. The couplers were fabricated using the silicon nitride platform of Lionix International. We also experimentally demonstrated an optical switch that is made by using two of these couplers in a Mach–Zehnder interferometer configuration. According to experimental results, this optical switch exhibits –10 dB of extinction ratio over the 1500–1600 nm wavelength range. Our results indicate that this new type of coupler holds great promise for various applications, including optical imaging, telecommunications, and reconfigurable photonic processors where compact, fabrication-tolerant, and wavelength-insensitive couplers are essential.
Keywords: tet_topic_waveguide

Separation Of Multi-Component Parts For Mechanical Recycling – Study About Basic Approaches Using A Heating Process - Hopp, Matthias; Schäffer, Leon

Dimensionierung und Optimierung von im FDM-Verfahren 3D-gedruckten Direktverschraubungen aus ABS - Moritzer, Elmar; Held, Christian; Hillemeyer, Johannes (Joining Plastic)

Mit der richtigen Auslegung zur sicheren Verbindung - Moritzer, Elmar; Held, Christian; Hopmann, C.; Kramer, M. (Kunststoffe)

Wie bewährt sich das duale berufliche Ausbildungssystem der industriellen Metall und Elektroausbildung unter Pandemiebedingungen? Lehrkräfte und Auszubildende reflektieren - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s): Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)

Reproducibility and Scattering in Additive Manufacturing: Results from a Round Robin on PBF-LB/M AlSi10Mg Alloy - Schneider, M.; Bettge, D.; Binder, M.; Dollmeier, K.; Dreyer, Malte; Hilgenberg, K.; Klöden, B.; Schlingmann, T.; Schmidt, J. (Practical Metallography)
Abstract The round robin test investigated the reliability users can expect for AlSi10Mg additive manufactured specimens by laser powder bed fusion through examining powder quality, process parameter, microstructure defects, strength and fatigue. Besides for one outlier, expected static material properties could be found. Optical microstructure inspection was beneficial to determine true porosity and porosity types to explain the occurring scatter in properties. Fractographic analyses reveal that the fatigue crack propagation starts at the rough as-built surface for all specimens. Statistical analysis of the scatter in fatigue using statistical derived safety factors concludes that at a stress of 36.87 MPa the fatigue limit of 10 7 cycles could be reached for all specimen with a survival probability of 99.999 %.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Event-Driven Programming of FPGA-accelerated ROS 2 Robotics Applications - Lienen, Christian; Platzner, Marco (2022 25th Euromicro Conference on Digital System Design (DSD))

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (Annales Henri Poincaré)
Abstract The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $$\mathbb {M}$$ M is a stochastic process that models a random perturbation of the geodesic flow. If $$\mathbb {M}$$ M is an orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the $$L^2$$ L 2 -spectrum of the infinitesimal generator of a time-rescaled version of the process converges to the Laplace spectrum of the base manifold.
Keywords: Mathematical Physics; Nuclear and High Energy Physics; Statistical and Nonlinear Physics

Ruelle–Pollicott resonances for manifolds with hyperbolic cusps - Guedes Bonthonneau, Yannick; Weich, Tobias (Journal of the European Mathematical Society)
Keywords: Applied Mathematics; General Mathematics

Soziotechnische Herausforderungen bei der Einführung von RPA managen - Hobscheidt, Daniela; Menzefricke, Jörn Steffen; Gabriel, Stefan; Kühn, Arno; Dumitrescu, Roman (Praxishandbuch Robotic Process Automation (RPA))

The adrenal steroid profile in adolescent depression: a valuable bio-readout? - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hauffa, Berthold P.; Hebebrand, Johannes; Grasemann, Corinna (Translational Psychiatry)
Abstract There is preliminary evidence that adrenal steroids other than cortisol may be valuable biomarkers for major depressive disorder (MDD). So far, studies have been conducted in adults only, and conclusions are limited, mainly due to small sample sizes. Therefore, the present study assessed whether adrenal steroids serve as biomarkers for adolescent MDD. In 261 depressed adolescents (170 females) treated at a single psychiatric hospital, serum adrenal steroids (progesterone, 17-hydroxyprogesterone, 21-deoxycortisol, 11-deoxycortisol, cortisol, cortisone, deoxycorticosterone, corticosterone) were determined by liquid chromatography-tandem mass spectrometry. Findings were compared to that of an age- and sex-matched reference cohort ( N = 255) by nonparametric analysis of variance. Nonparametric receiver operating characteristics (ROC) analyses were conducted to evaluate the diagnostic performance of single steroids and steroid ratios to classify depression status. Sensitivity analyses considered important confounders of adrenal functioning, and ROC results were verified by cross-validation. Compared to the reference cohort, levels of deoxycorticosterone and 21-deoxycortisol were decreased ( P < 0.001). All other glucocorticoid- and mineralocorticoid-related steroids were increased ( P < 0.001). The corticosterone to deoxycorticosterone ratio evidenced excellent classification characteristics, especially in females (AUC: 0.957; sensitivity: 0.902; specificity: 0.891). The adrenal steroid metabolome qualifies as a bio-readout reflecting adolescent MDD by a distinct steroid pattern that indicates dysfunction of the hypothalamus–pituitary–adrenal axis. Moreover, the corticosterone to deoxycorticosterone ratio may prospectively qualify to contribute to precision medicine in psychiatry by identifying those patients who might benefit from antiglucocorticoid treatment or those at risk for recurrence when adrenal dysfunction has not resolved.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. - Caruso, Carina; Neuweg, Georg Hans; Wagner, Michael; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung / Teacher training; Mentoring; Internship; Professionalization; Theory-practice-relation

Inwiefern ist die Professionalisierung in Praxisphasen schulformspezifisch? - Caruso, Carina; Seifert, Andreas (Österreichische Religionspädagogische Forum)
Im Zentrum dieses Beitrags stehen Ergebnisse der Messung pädagogischer Kompetenzen Studierender der Theologie, die das Praxissemester in Deutschland absolviert haben. Das bildungswissenschaftliche Wissen, Kompetenzselbsteinschätzungen und ihre Entwicklung sowie die Einschätzung der im Praxissemester erreichten Ziele Studierender werden dabei unter Berücksichtigung der Ausrichtung des Lehramtsstudiums auf eine Schulform betrachtet. Um die Ergebnisse der Messung bildungswissenschaftlichen Wissens und die der Messung von Kompetenzselbsteinschätzungen zu kontextualisieren (N = 304), wird zuerst die Relevanz des (bildungswissenschaftlichen) Wissens als Ausgangspunkt des Könnens herausgearbeitet. Daran anschließend werden Befunde zur schulformspezifischen Professionalisierung resümiert. Anschließend werden Hypothesen hergeleitet, die Anlage der Studie sowie die Testinstrumente vorge- stellt, die Ergebnisse präsentiert und diskutiert. Die Ergebnisse zeigen wider Erwarten, dass sich weder das bildungswissenschaftliche Wissen, die Kompetenzselbsteinschätzungen und ihre Entwicklung noch die Einschätzung der im Praxissemester erreichten Ziele angehender Lehrkräfte in Abhängigkeit der Schulformen unterscheiden. Die Diskussion bezieht sich u.a. auf die Struktur der Lehramtsstudiengänge, die Denkfiguren zur Entwicklung von Können und die Konzeption der Messinstrumente.
Keywords: Bildungswissenschaftliches Wissen; Kompetenzmessung; Kompetenzselbsteinschätzung; Praxissemester; Professionalisierung / competence measurement; competence self-assessment; educational knowledge; internship; professionalization

Das Belastungserleben von Lehramtsanwärterinnen und -anwärtern im Vorbereitungsdienst - Bruns, Marike; Caruso, Carina; Ackermann, Luisa (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Die Ausbildung von Lehrkräften teilt sich in Studium und Vorbereitungsdienst. Während im Studium Wissen grundgelegt wird, dient der Vorbereitungsdienst, der überwiegend in der Schule stattfindet, dem Erwerb praktischer Kompetenzen, was den Rückbezug auf theoretisch fundierte Kenntnisse und den Aufbau erfahrungsbasierten Wissens umfasst. Die Maßnahmen zur Eindämmung der Corona-Pandemie verändern nicht nur den Schulalltag, sondern haben auch Einfluss auf die Kompetenzentwicklung angehender Lehrkräfte im Vorbereitungsdienst, die ihre Berufsausbildung unter veränderten Rahmenbedingungen durchführen müssen. Die aktuellen Rahmenbedingungen können u. a. aufgrund fehlender bzw. eingeschränkter Praxiserfahrungen eine reguläre Ausbildung erschweren, was zu einem erhöhten Belastungsempfinden der angehenden Lehrkräfte beitragen kann. In diesem Beitrag wird Bezug genommen auf Daten einer explorativen Interviewstudie mit Lehramtsanwärterinnen und -anwärtern aus Nordrhein-Westfalen (N = 19), die während der Pandemie im Jahr 2020 ihren Vorbereitungsdienst absolviert haben. Es wird dabei den Fragen nachgegangen, welche Belastungsfaktoren im Zusammenhang mit der Corona-Pandemie während des Vorbereitungsdienstes auftreten können und inwieweit sich angehende Lehrkräfte während ihres Vorbereitungsdienstes vor dem Hintergrund der aktuellen Rahmenbedingungen infolge der Corona-Pandemie als belastet erleben.
Keywords: Corona-Pandemie; Lehramtsanwärter:innen; Lehrer:innenausbildung; Professionalisierung; Vorbereitungsdienst / corona pandemic; prospective teachers; teacher training; professionalization; preparatory service

Von der Not zur Tugend!? - Caruso, Carina; Bruns, Marike; Harteis, Christian (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s) Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Der Begriff der „Zwangsdigitalisierung“ beschreibt, dass als eine Folge der Corona-Pandemie Präsenzformate durch digital gestützte Settings ersetzt werden sowie Alter- nativen zur Kommunikation und für das gemeinsame Arbeiten und Lernen in Präsenz gefunden werden mussten. Digital gestützte Lehr-Lernsettings scheinen seit dem ersten Lockdown sowohl an Schulen als auch an Hochschulen eine Möglichkeit dafür darzustellen, die Lern- und Entwicklungsprozesse (z. B. von Schülerinnen und Schülern, angehenden Lehrkräften) trotz physischer Distanz weiterzuführen. In diesem Beitrag werden die mit der Zwangsdigitalisierung an den Hochschulen verbundenen Chancen und Grenzen für die Entwicklung digitalisierungsbezogener Kompetenzen angehender Lehrkräfte herausgearbeitet. Dabei richtet sich der Blick auf den Wert von Erfahrungen für Lernen und Entwicklung. Zudem wird, gemäß der den Angebots-Nutzungs-Modellen inhärenten Logik einer „Wirkkette“, Bezug genommen auf Perspektiven von Studierenden, deren prospektiven Schülerinnen und Schülern sowie von Dozierenden.
Keywords: Hochschullehre; Lehrer:innenausbildung; Medienkompetenz / teacher education; teaching at university; media literacy

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for researching professional learning and development: Challenges, applications and empirical illustrations)
Q is an exploratory method used to elicit discrete patterns of subjectivity (e.g., subjective theories, beliefs). To be more concrete, Q method aims to identify homogeneous latent clusters of viewpoints towards a certain topic from a larger more heterogeneous set of (a priori unknown) different viewpoints held by respondents in the population. For this purpose, study participants are asked to sort qualitative statements concerning a certain topic (e.g., their beliefs toward something) into a grid roughly following a normal distribution indicating whether they agree or disagree with the given propositions. This results in a so-called Q-sort for each participant that then can be fed into a factor analysis that compares the different Q-sorts and groups them by similarity. In the first part of the chapter, Q method is introduced. The second part of the chapter describes a small study focusing on student teachers and their perspectives concerning upcoming long-term school internships.
Keywords: Q method; Subjectivity; Internships; Teacher education; Q sort

Zum Ausmaß und Zusammenhang der unterrichtsbezogenen Nutzung digitaler Medien mit der Medienkompetenz von Lehrkräften unter Berücksichtigung von Hintergrundmerkmalen - Caruso, Carina; Heldt, Melanie; Drossel, Kerstin (Lehrerbildung auf dem Prüfstand)

Pädagogische Kompetenz als Ausgangspunkt beruflichen Könnens!? Ergebnisse der Kompetenzmessung angehender Lehrkräfte unter Berücksichtigung individueller Voraussetzungen - Caruso, Carina; Seifert, Andreas (Religionspädagogische Beiträge. Journal for Religion in Education)
Im Zentrum dieses Beitrags stehen Ergebnisse der Messung pädagogischer Kompetenzen Studierender. Dabei werden sowohl das bildungswissenschaftliche Wissen als auch die Entwicklung der Kompetenzselbsteinschätzungen in den Bereichen Unterrichten, Erziehen, Beurteilen und Innovieren unter Berücksichtigung individueller Voraussetzungen (Alter, Geschlecht, Abiturnote, Bachelornote, Konfession) betrachtet. Um die Ergebnisse hinsichtlich ihrer Bedeutung für die Professionalisierung angehender Lehrkräfte diskutieren zu können, wird, den empirischen Erkenntnissen voranstehend, die Bedeutung von Wissen für berufliches Können herausgearbeitet. Daran anschließend werden Hypothesen hergeleitet, die Anlage der Studie sowie die Testinstrumente vorgestellt, die Ergebnisse präsentiert und diskutiert. Die Ergebnisse zeigen, dass die Abitur- und Bachelornote die Varianz hinsichtlich des pädagogischen Wissens aufklären, sich eine signifikante Entwicklung der Kompetenzselbsteinschätzungen angehender Lehrkräfte feststellen lässt, aber sich angehende Religionslehrkräfte kaum von anderen Studierenden unterscheiden. Die Diskussion nimmt u. a. Rückbezug auf die Denkfiguren zur Entwicklung beruflichen Könnens und benennt Limitationen, die mit der Studie und Kompetenzmessungen verbunden sind. Daran schließt die Formulierung eines Ausblicks an. Der Beitrag zielt insbesondere darauf, repräsentative Ergebnisse der Kompetenzmessung zu präsentieren und dabei potenzielle Einflussfaktoren auf die studentische Kompetenzentwicklung zu beleuchten. Ein dadurch angereichertes Konglomerat belastbarer Erkenntnisse zielt darauf, langfristig zur Ableitung lehrerbildungsdidaktischer Überlegungen herangezogen werden zu können, die die studentische Professionalisierung unterstützen.
Keywords: Bildungswissenschaftliches Wissen; Kompetenzmessung; Kompetenzselbsteinschätzung; Praxissemester; Professionalisierung / competence measurement; competence self-assessment; educational knowledge; internship; professionalization

Die Relevanz von Mentor*innen für die Professionalisierung von angehenden Lehrkräften im Praxissemester: Forschungsdesiderate und Handlungsoptionen - Caruso, Carina; Goller, Michael (Die Deutsche Schule)
Im Praxissemester (PS) sind Mentor*innen für Studierende wichtige Bezugspersonen, die sie u.a. bei der Planung, Durchführung und Reflexion von Unterricht begleiten. Während z.B. zur Kompetenzentwicklung Studierender im PS mehrere Erkenntnisse vorliegen, ist die Perspektive von Mentor*innen bisher wenig untersucht. Dieser Bericht zielt darauf, die Relevanz von Mentor*innen herauszuarbeiten, Forschungsdesiderate zu umreißen und Handlungsoptionen aufzuzeigen.
Keywords: Mentoring; Praxissemester; Professionalisierung / internships; mentoring; professionalisation

Zur rückblickenden Beurteilung von Fortbildungserfahrungen - Caruso, Carina (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Im Artikel werden die Relevanz von Lehrer*innenfortbildungen für die Professionalität und Expertise von Lehrkräften beschrieben sowie Forschungsergebnisse zu Lehrer*innenfortbildungen zusammengefasst. Im Zentrum des Beitrags stehen Ergebnisse einer Interviewstudie mit Lehrkräften, die Einblicke in die aktuelle Situation und Praxis von Lehrer*innenfortbildungen aus Sicht von Lehrkräften geben. Dabei werden folgende Fragestellungen aufgegriffen, indem die explorative Studie die Wahrnehmung von Fortbildungsveranstaltungen durch Lehrkräfte erhebt und darstellt: Wie bewerten Lehrkräfte die Rahmenbedingungen externer Lehrer*innenfortbildungen? Was sind aus Sicht von Lehrkräften Aspekte guter bzw. schlechter Fortbildungen? Was wünschen sich Lehrkräfte in Bezug auf die Planung, Gestaltung und Durchführung von Fortbildungen? Nach der Diskussion der Befunde endet der Beitrag mit einem Fazit.
Keywords: Expertise; Lehrerbildung; Professionalisierung; Lehrerfortbildung

Der technische Fortschritt und seine Implikationen aus pädagogischer Perspektive - Caruso, Carina; Martin, Alexander (Digitalisierungsbezogene Kompetenzen fördern: Herausforderungen, Ansätze und Entwicklungsfelder im Kontext von Schule und Hochschule)
Technologien beeinflussen verschiedene Bereiche des menschlichen Lebens. Gegenwärtig kommt insbesondere digitalen Technologien ein hoher Stellenwert zu, der sich u. a. dadurch auszeichnet, dass die Nutzung digitaler Technologien sowohl den privaten bzw. informellen als auch den beruflichen bzw. formellen Lebensraum betrifft. Diese Omnipräsenz digitaler Technologien im menschlichen Alltag macht digitalisierungsbezogene Kompetenzen zu einer Voraussetzung für eine selbstbestimmte gesellschaftliche Teilhabe und ist somit auch eine zentrale Zielperspektive schulischer Bildungs- und Erziehungsprozesse. Lehrkräfte, die Schüler*innen auf das Arbeiten und Leben in einer digital vernetzten Welt vorbereiten sollen, stehen deshalb vor einer doppelten Herausforderung: einerseits – wie jeder Mensch – sich selbst angesichts der Digitalisierung zurecht zu finden und entsprechende Medienkompetenzen auszubilden und andererseits medienpädagogische und digitalisierungsbezogene Kompetenzen zu entwickeln, um Lerngelegenheiten für den Unterricht konzipieren und bereitstellen zu können, die Schüler*innen den Erwerb von Medienkompetenzen ermöglichen. Die Lehrer*innenbildung in Deutschland umfasst drei Phasen: Studium, Vorbereitungsdienst und Fort- und Weiterbildung. Digitalisierungsbezogene Kompetenzen sollen angehende Lehrkräfte schon im Studium erwerben und in den anschließenden Phasen weiterentwickeln. In diesem Beitrag werden zunächst Merkmale einer digital vernetzten Welt als Ausgangs- und Bezugsunkte für Lern- und Bildungsprozesse beschrieben (Kap. 2). Daran anschließend werden Kompetenzbereiche erläutert, denen auf dieser Grundlage ein hoher Stellenwert zukommt (Kap. 3). Nach der Herleitung der Forschungsfrage (Kap. 4) und der Beschreibung der Methode (Kap. 5) werden exemplarische Ergebnisse einer Inhaltsanalyse von Studienordnungen nordrhein-westfälischer Lehramtsstudiengänge dargestellt (Kap. 6) und diskutiert (Kap. 7). Die Ergebnisse der Analyse der Studienordnungen der Fächer Katholische Theologie bzw. Unterrichtsfach Pädagogik zeigen, dass angehenden Lehrkräften zum Teil curricular verankerte Lerngelegenheiten fehlen, um in der ersten Phase der Lehrer*innenbildung digitalisierungsbezogene Kompetenzen zu erwerben.

L_2 error estimates for polynomial discrete penalized least-squares approximation on the sphere from noisy data - Hesse, Kerstin; Le Gia, Quoc Thong (Journal of Computational and Applied Mathematics)
Keywords: Applied Mathematics; Computational Mathematics

Die Vielseitigkeit von Beschichtungen im Spritzgießwerkzeug- und Formenbau - Moritzer, Elmar; Rauen, Dennis; Schilp, Catharina; Scholle, Maximilian (Zeitschrift Kunststofftechnik)

Situation-specific Development of Business Models within Software Ecosystems - Gottschalk, Sebastian
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a challenging activity. On the one hand, various tasks of business model development methods (BMDMs) need to be performed. On the other hand, different decisions for the business models (BMs) need to be made. Both have to fit the changeable situation of the organization in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, the BMDMs and the BMs must be developed situation-specific. In this thesis, we conduct a design science research study to design a novel approach for the situation-specific development of business models with three stages. In the first stage, we create a method repository with method fragments for the BMDMs and a canvas model repository with modeling fragments for the BMs. Both repositories are filled by the knowledge of domain experts. Out of these repositories, in the second stage, situation-specific BMDMs for developing situation-specific BMs are composed by a method engineer based on the changeable situation of the organization and enacted by a business developer. The business developer collaborates with other stakeholders during the enaction to create artifacts. Moreover, in the third stage, he receives IT support, provided by development support engineers, in different development steps.

Qualifizierung mechanischer Fügeverfahren für Batteriekästen - Han, Daxin; Meschut, Gerson

Seizing the Opportunity for Automation—How Traffic Density Determines Truck Drivers' Use of Cruise Control - Hoffmann, Christin; Thommes, Kirsten (IEEE Transactions on Human-Machine Systems)
Keywords: Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Signal Processing; Control and Systems Engineering; Human Factors and Ergonomics

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Germany - Schönhärl, Korinna; Osterloh-Konrad, Christine (History and taxation. The dialectical relationship between taxation and the political balance of power: 2021 EATLP Congress Antwerp, 3-4 June 2021)

Interpunktion - Tophinke, Doris (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)